The Effect of Knowledge Management, Compensation, and Spirit Work on Employee Performance at Villa Mahalini Seminyak Bali - A.A. Istri Agung Maheswari; I Gede Agus Eka Suputra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Knowledge Management is a systematic process of discovering, selecting, organizing, extracting and presenting knowledge in a particular way, so that workers are able to utilize and enhance the mastery of knowledge in a specific field of study, and then there is the institutionalization process for the knowledge created into the firm's knowledge. compensation is defined as what an employee receives as a reward for their treatment, which is compromised by the compensation process. The compensation process itself is a network of various subprocesses to provide compensation to employees for the performance of the work and to motivate them to achieve the desired level of achievement. Spirit Work is the desire and seriousness of a person to do their job well and to be disciplined to achieve maximum work performance. Performance is the result of work both in quality and quantity achieved by a person in carrying out the task according to the responsibility given. The data used in this study is primary data through the spread of questionnaires and secondary data from previous research, literature, print media (newspapers and magazines) and electronic media (internet). The sampling technique using the liker scale, the number of samples used in the study amounted to 50 people or respondents. Data analysis techniques used in this study are Classical Assumption Test, Multiple Linear Regression Analysis. The result of t test in the research that is the management knowledge to the employee performance is 0,217, the compensation to employee performance equal to 0,381, spirit work to employee performance equal to 0,169. Based on the determination coefficient test that is equal to 95.1 percent employee performance is influenced by knowledge management variables (X1), Compensation (X2) and spirit work (X3). The rest of 4.9 percent is influenced by other variables not examined in this study.